Effect of a Multi-Nutrient Over-the-Counter Supplement on Changes in Metabolic Rate and Markers of Lipolysis. (4th May 2017) - Ziegenfuss, Tim N.; Lopez, Hector L.; Sandrock, Jennifer E.; Kedia, A. William; Habowski, Scott; Kerksick, Chad
ABSTRACT: Using a prospective, randomized, double-blind, crossover study design, fifteen healthy male ( n = 8) and female ( n = 7) participants (mean ± standard deviation (SD): 28.3 ± 6.1 yr, 176.3 ± 11.4 cm, 89.8 ± 21.7 kg, 28.5 ± 4.8 kg/m 2 ) completed this study. Two testing sessions occurred after an overnight fast and refraining from physical exercise. Prior to and 60, 120, and 180 minutes after single dose ingestion of placebo (PLA) or a Thermogenic Supplement (TS), visual analog scales (VAS), resting metabolic rate (VO2 ), and venous blood were collected. Resting heart rate and blood pressures were collected before, and 30, 60, 90, 120, 150 and 180 minutes after PLA or TS ingestion. Significant group × time interactions were found for VO2 with TS experiencing significant ( p < 0.05) increases 60 and 120 minutes after ingestion. Respiratory quotient values tended to be lower 180 minutes ( p = 0.07) after TS ingestion. TS group reported increased energy 60 minutes ( p < 0.05) after ingestion. No interactions were reported for resting heart rate or blood pressure. Significant within-group reductions in systolic blood pressure were noted for PLA, while resting heart rates were significantly lower in TS 30 and 60 minutes after ingestion. An interaction for epinephrine ( p = 0.02) was found, while no changes were reported for norepinephrine and dopamine. Dependent t-tests using area under the curve calculations revealed higher AUC values for epinephrine in TS compared to PLA ( p = 0.001). In conclusion, ingestion of a single dose of TS increased oxygen consumption, epinephrine and energy levels, while substrate oxidation tended to change in comparison to a placebo. No adverse responses were reported.